Characterization of carbon fiber reinforced polymer strengthened concrete and gap detection with a piezoelectric-based sensory technique. (January 2019) - Giri, Paritosh; Kharkovsky, Sergey; Zhu, Xinqun; Clark, Simon Martin; Taheri, Shima; Samali, Bijan
In this article, a piezoelectric-based sensory technique is proposed for detection of the gap between surfaces of a carbon fiber reinforced polymer plate and a concrete specimen and characterization of shrinkage of early-age concrete. The proposed technique uses the propagation properties of the guided waves in the carbon fiber reinforced polymer plate excited and received by piezoelectric transducers attached to an external surface of the carbon fiber reinforced polymer–strengthened concrete specimen. Measurements are conducted with fresh and hardened early-age concrete specimens and two carbon fiber reinforced polymer plates at different gaps. A piezoelectric actuator is excited using a sine burst signal, and the generated wave is received by a sensor after propagation along the specimen. The received signal at different gap values is used to detect a gap. To quantify the gap, damage indices, including correlation coefficient, peak-to-peak amplitude of resultant signal, and root-mean-square deviation, are used. The shrinkage of concrete is detected and predicted by comparing the damage indices at different gaps with the indices at different stages of early-age concrete. The proposed technique is relatively simple method using small transducers. It is one-sided, non-destructive, and cost-effective solution for gap detection and concrete characterization.